An unusual cause of altered mental status: the importance of monitoring a patient's blood pressure. (5th August 2014) - Mathew, Jacob; Koo, Matthew; Crook, Irina R; Jahanmir, Jay
Abstract : A 73-year-old man presented to the emergency room for acute onset altered mental status. The initial work-up yielded no definitive cause. An MRI demonstrated lesions in the bilateral posterior occipital lobes (not noted on an earlier MRI obtained from an outside institution) that were suggestive of posterior reversible encephalopathy syndrome (PRES). He had a history of Parkinson's disease complicated by autonomic instability (wide blood pressure fluctuations) that was medically controlled in the outpatient setting. During the early course of his hospitalisation, he again displayed wide blood pressure fluctuations. After his blood pressure stabilised, his mental status eventually improved to baseline. A repeat MRI obtained demonstrated near-complete resolution of the previously noted lesions and confirmed the diagnosis of PRES.